Effectiveness of Coronavirus Disease 2019 (COVID-19) Vaccination Against Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) Infection Among Residents of US Nursing Homes Before and During the Delta Variant Predominance, December 2020–November 2021 . (20th July 2022) - Hatfield, Kelly M; Baggs, James; Wolford, Hannah; Fang, Michael; Sattar, Ammarah A; Montgomery, Kelsey S; Jin, Steven; Jernigan, John; Pilishvili, Tamara
Abstract: Background: Residents of nursing homes experience disproportionate morbidity and mortality related to coronavirus disease 2019 (COVID-19) and were prioritized for vaccine introduction. We evaluated COVID-19 vaccine effectiveness (VE) in preventing severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infections among nursing home residents. Methods: We used a retrospective cohort of 4315 nursing home residents during 14 December 2020–9 November 2021. A Cox proportional hazards model was used to estimate hazard ratios comparing residents with a completed vaccination series with unvaccinated among those with and without prior SARS-CoV-2 infection, by vaccine product, and by time period. Results: Overall adjusted VE was 58% (95% confidence interval [CI], 44% to 69%) among residents without a history of SARS-CoV-2 infection. During the pre-Delta period, the VE within 150 days of receipt of the second dose of Pfizer-BioNTech (67%; 95% CI, 40% to 82%) and Moderna (75%; 95% CI, 32% to 91%) was similar. During the Delta period, VE measured >150 days after the second dose was 33% (95% CI, −2% to 56%) for Pfizer-BioNTech and 77% (95% CI, 48% to 91%) for Moderna. Rates of infection were 78% lower (95% CI, 67% to 85%) among residents with prior SARS-CoV-2 infection and completed vaccination series compared with unvaccinated residents without a history of SARS-CoV-2 infection. Conclusions: COVID-19 vaccines were effective in preventing SARS-CoV-2 infections among nursing home residents, and history of prior SARS-CoV-2 infection provided additional protection. Maintaining high coverage of recommended doses of COVID-19 vaccines remains a critical tool for preventing infections in nursing homes. Abstract : Coronavirus disease 2019 vaccines were effective in preventing severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infections among a large cohort of more than 4000 nursing home residents. History of prior SARS-CoV-2 infection provided additional protection, and effectiveness more than 150 days after completed vaccination was different by messenger RNA vaccine product.